2000
DOI: 10.1002/1521-3765(20001002)6:19<3517::aid-chem3517>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Highly β‐Selective Epoxidation of Δ 5 ‐Unsaturated Steroids Catalyzed by Ketones

Abstract: A general catalytic and environmentally friendly method for beta-epoxidation of delta5-unsaturated steroids has been developed, which uses ketones as the catalysts and Oxone as the terminal oxidant. A whole range of delta5-unsaturated steroids, which bear different functional groups such as hydroxyl, carbonyl, acetyl, or ketal, as well as different side chains, were conveniently converted to the corresponding synthetically and biologically interesting 5beta,5beta-epoxides with excellent beta-selectivities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…This is because peracid epoxidation follows a concerted pathway via spiro transition states (α‐transition and β‐transition state). In the β‐transition state, there are steric interactions between the m ‐CPBA and the C‐10 angular methyl group during epoxidation of 3β‐substituted Δ 5 steroids, while similar steric hindrance occurs in the both β‐transition and the α‐transition state during epoxidation of 3α‐substituted steroids .…”
Section: Resultsmentioning
confidence: 99%
“…This is because peracid epoxidation follows a concerted pathway via spiro transition states (α‐transition and β‐transition state). In the β‐transition state, there are steric interactions between the m ‐CPBA and the C‐10 angular methyl group during epoxidation of 3β‐substituted Δ 5 steroids, while similar steric hindrance occurs in the both β‐transition and the α‐transition state during epoxidation of 3α‐substituted steroids .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, other 5β,6β-epoxysteroids (Scheme 2) were efficiently prepared using chiral ketones [e.g. 1,1,3(S),5(R)-tetramethyl-4oxo-2(R),6(S)-diphenylpiperidinium triflate] as organocatalysts and Oxone TM as oxidant [72]. More recently, Dansey et al [73] reported the application of a chiral and bulky fructose-derived ketone as catalyst also combined with Oxone TM for the regio-and stereoselective epoxidation of a diene A-homosteroid that occurred in the steroidal A-ring and afforded the corresponding β-epoxide as the only product in 35% yield [73].…”
Section: Epoxidationmentioning
confidence: 99%
“…Another asymmetric epoxidation was also reported using Oxone with keto bile acids 142 α-and β-Epoxides of cholesterol are the autooxidation products of cholesterol in vivo and both are cytotoxic and mutagenic. Yang and Jiao reported highly β-selective epoxidation of 5 -unsaturated steroids catalyzed by ketones 144 . Organic oxidants such as m-CPBA give α-epoxides as the major epoxidation products for the epoxidation of 3β-substituted 5 -steroids, but they show poor selectivities for the epoxidation of 3α-substituted 5 -steroids.…”
Section: E Potassium Peroxymonosulfatementioning
confidence: 99%